Boondoogles and Expropriation : Rent-seeking and Policy Distortion when Property Rights are Insecure - Keefer, Philip; Knack, Stephen (World Bank, Washington, DC, 2014)
Most analyses of property rights and economic development point to the negative influence of insecure property rights on private investment. The authors focus instead on the largely unexamined effects of insecure property rights on government policy choices. They identify one significant anomaly-dramatically higher public investment in countries with insecure property rights-and use it to make the following broad claims about insecure property rights; 1) They increase rent-seeking. 2) They may reduce the incentives of governments to use tax revenues for productive purposes, such as public investment. 3) They do so whether one regards the principal problem of insecure property rights as the maintenance of law and order, which government spending can potentially remedy, or as the threat of expropriation by government itself, and therefore not remediable by government spending. The authors present substantial empirical evidence to support these claims.